SPECIFIC METHODS AND TASKS FOR THE PHYSICAL DEVELOPMENT OF PRIMARY SCHOOL STUDENTS WITH THE HELP OF GAMES - Parmonov Akmal Abdupattayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article reveals specific ways and tasks for the physical development of Primary School students using games.